একাত্তরের রণাঙ্গন, গেরিলাযুদ্ধ ও হেমায়েতবাহিনী - উল্লাহ, মোহাম্মদ সফিক. 1941-
Role of a group of revolutionaries under the leadership of Hemāẏetauddina, b. 1941, in the liberation war of Bangladesh, 1971.